Mitigasi Bencana pada Area Rentan Banjir di Kabupaten Dharmasraya - Ismayani, Nina; Putri, Desi Eka; Febrianto, Hary; Sary, Ayu Kurnia (LaGeografia, 2024)
Based on the RTRW of Dharmasraya Regency, the hydrological aspects reveal numerous river basins and relatively gentle slopes, leading to frequent flooding during the rainy season. This study aims to identify flood vulnerability levels in Dharmasraya Regency and develop effective mitigation strategies. Using purposive sampling, data were analyzed descriptively and quantitatively through Overlay and Scoring techniques, categorizing flood vulnerability into three levels: slightly vulnerable (16,037.18 ha), vulnerable (68,982.47 ha), and highly vulnerable (168,920.24 ha). The proposed mitigation strategies include structural approaches such as constructing embankments and evacuation routes, and non-structural approaches like public awareness campaigns and disaster management training. This research contributes to developing more adaptive and context-specific disaster mitigation methods for regions with similar hydrological and topographical characteristics, offering a broader application of mitigation approaches in regional contexts. The findings enrich the literature on natural disaster mitigation in flood-prone areas and guide stakeholders in reducing flood risk in Dharmasraya Regency. AbstrakBerdasarkan RTRW Kabupaten Dharmasraya, aspek hidrologi menunjukkan banyak daerah aliran sungai dan kemiringan landai, menyebabkan banjir sering terjadi selama musim hujan. Penelitian ini bertujuan mengidentifikasi tingkat kerentanan banjir di Kabupaten Dharmasraya dan mengembangkan strategi mitigasi yang efektif. Dengan metode purposive sampling, data dianalisis secara deskriptif kuantitatif menggunakan teknik Overlay dan Skoring, memetakan kerentanan banjir ke dalam tiga kategori: agak rentan (16.037,18 ha), rentan (68.982,47 ha), dan sangat rentan (168.920,24 ha). Strategi mitigasi meliputi pendekatan struktural, seperti pembangunan tanggul dan jalur evakuasi, serta pendekatan non-struktural, seperti penyuluhan dan pelatihan pengelolaan bencana banjir. Penelitian ini berkontribusi pada pengembangan metode mitigasi bencana yang lebih adaptif dan relevan untuk wilayah dengan karakteristik hidrologi dan topografi serupa, serta menawarkan pendekatan mitigasi yang dapat diterapkan secara luas dalam konteks regional. Temuan ini memperkaya literatur tentang mitigasi bencana alam di daerah rawan banjir dan memberikan panduan bagi pemangku kepentingan dalam mengurangi risiko banjir di Kabupaten Dharmasraya.